The Role of Scientific Approaches in Enhancing Natural Science Learning Outcomes in Indonesian Primary Schools - Akhlis, Noor; Sukri, Moh.; Yunus, A (ISEJ : Indonesian Science Education Journal, 2024)
Improving the quality of science education in primary schools has become a central concern in Indonesia, where international assessments continue to indicate lower achievement levels compared to neighboring countries, thus underscoring the importance of adopting pedagogical approaches that foster inquiry and scientific reasoning from an early age. This study aimed to analyze the urgency of implementing the scientific approach in natural science learning at the elementary school level by situating it within the framework of the 2013 Curriculum. Employing a qualitative descriptive design, data were collected from policy documents, peer-reviewed journals, and scholarly books and analyzed through thematic analysis to identify key patterns, challenges, and opportunities related to the integration of inquiry-oriented instruction. The results reveal that while the scientific approach is conceptually aligned with international standards of inquiry-based learning and has the potential to enhance student engagement and critical thinking, its implementation in Indonesian classrooms remains constrained by systemic barriers such as limited teacher preparation, insufficient resources, and exam-driven teaching practices. The discussion highlights that bridging the gap between curricular policy and classroom practice requires sustained professional development, contextual adaptation of teaching strategies, and supportive educational policies that prioritize inquiry processes over rote memorization. This study contributes to the literature by offering novel insights into the conceptual and practical urgency of the scientific approach in developing country contexts and implies that successful integration could not only improve student learning outcomes but also strengthen the foundations of scientific literacy essential for twenty-first century competencies.